UPAYA PENGAMATAN PELAKSANAAN PEMBELAJARAN TERPADU MODEL CONNECTED LEARNING (MCL) - Riatun Riatun (JURNAL TEMATIK, 2020)
The purpose of this study was to determine the learning outcomes obtained by teachers and students after using the integrated learning model Conneted Learning in State Elementary Schools 097358 Negri Lawan. This type of research is a school action carried out as much as 2 cycles. Data collection methods are used, observation sheets, observations, and photos. From the analysis obtained early learning or before being given an action, it can be seen that the average grade of the class is 66.9 and the percentage of the category is quite 100%, either 0% / In the first cycle of action with the official visit of the education supervisor at SDN 097358 Negri Selawan obtained an average value class 76.1 with 0% enough category percentage and 100% enough category. This shows an increase in pre-cycle test results both in terms of grade averages and observations of learning implementation. In the second cycle of action by visiting educational supervisors, the average value of the class increased by 91.9 and the observation value of learning implementation increased.